Centre for Advanced Studies – CAS - Craglia, M; Gómez Gutiérrez, E; Glovičko, J; Manzan , S; Charisi , V; Calzada, I; Consoli , S; Hradec, J; Micheli, M; Tolan, S; Miron, M; Tosetti, E; et al. (European Commission, DG Joint Research Centre, 2020)
The JRC's Centre for Advanced Studies (CAS) was created in 2016 to help improve and bridge the interface between science and policy in order to enhance the JRC's capacity to better inform and influence the regulatory frameworks needed to address the new and emerging societal challenges confronting the EU and our societies as a whole.